ON THE COMBINATION OF MMP WITH MOM - Hafner, Ch. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
The Multiple Multipole Program (MMP) [1] is based on the Generalized Multipole Technique (GMT) [2]. This method lies between a purely analytic solution and the well-known Method of Moments (MoM) [3]. The goal of this paper is to demonstrate how a combination of MMP with MoM can be achieved for obtaining more powerful codes. The combination presented here is based on an implementation of rooftop functions as a new type of basis function in 3D MMP. Since users of this code are often interested in the close near-field, a special implementation of rooftop functions is presented and tested. (Vol. 9, No. 3 (1994), Special Issue on Generalized Multipole Technique (GMT), pp 18-27]